Response of sediment bacterial community to triclosan in subtropical freshwater benthic microcosms. (May 2019) - Peng, Feng-Jiao; Diepens, Noël J.; Pan, Chang-Gui; Ying, Guang-Guo; Salvito, Daniel; Selck, Henriette; Van den Brink, Paul J.
Abstract: The response of sediment bacterial communities in subtropical freshwater benthic microcosms to sediment-associated triclosan (TCS; 28 d exposure) was analysed using Illumina high-throughput sequencing. This study highlights the interactive effects of TCS and the presence of benthic macroinvertebrates ( Limnodrilus hoffmeisteri and Viviparidae bellamya ) on sediment bacterial communities. Our results show that TCS alone significantly altered the taxonomic composition and decreased alpha diversity of sediment bacterial communities at concentrations ≥80 μg TCS/g dry weight (dw) sediment (sed). Regarding dominant phyla, TCS significantly reduced the relative abundance of Bacteroidetes and Firmicutes at these concentrations, whereas the relative abundance of Chloroflexi and Cyanobacteria increased. In the presence of benthic macroinvertebrates, the sediment bacterial community was affected by 8 μg TCS/g dw sed as well. However, the presence of benthic macroinvertebrates did not cause measurable changes to bacterial community in unspiked (i.e., control) sediment. These results indicate that TCS alone would not alter the sediment bacterial community at environmentally relevant concentrations (up till 8 μg/g dw sed), but may have an effect in combination with the presence of benthic macroinvertebrates. Therefore, we recommend to include benthic macroinvertebrates when assessing the response of sediment bacterial communities during exposure to environmental stress such as organic contaminants. Graphical abstract: Image 1 Highlights: 80 μg TCS/g dw alone altered sediment bacterial community composition and structure. 80 μg TCS/g dw alone decreased alpha diversity of sediment bacterial community. Benthic macroinvertebrates enhanced TCS activity to sediment bacterial community.